2021
DOI: 10.1002/ps.6290
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the proteasome reduces molecular and biological impacts of the natural product insecticide, spinosad

Abstract: BACKGROUND Insecticide targets are often identified by mutations that confer resistance, but the intricacies of insecticide binding and downstream processes leading to insect death often remain obscure. Mutations in α6‐like nicotinic acetylcholine receptor subunit genes have been associated with high levels of resistance to spinosad in many insect species, including Drosophila melanogaster. Here, we aimed to expand our understanding of the effects of the natural product insecticide spinosad on its protein targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…No increase in the area occupied by lysosomes was observed after exposure to imidacloprid, showing that this is a spinosad specific response ( Figure 2 – figure supplement 1 ). These observations, in combination with the findings of Nguyen et al (2021) suggested that binding of spinosad to Dα6 nAChRs may promote their trafficking to lysosomes. To investigate this hypothesis, the brains of larvae expressing a fluorescently (CFP) tagged Dα6 nAChR subunit were stained with LysoTracker.…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…No increase in the area occupied by lysosomes was observed after exposure to imidacloprid, showing that this is a spinosad specific response ( Figure 2 – figure supplement 1 ). These observations, in combination with the findings of Nguyen et al (2021) suggested that binding of spinosad to Dα6 nAChRs may promote their trafficking to lysosomes. To investigate this hypothesis, the brains of larvae expressing a fluorescently (CFP) tagged Dα6 nAChR subunit were stained with LysoTracker.…”
Section: Resultsmentioning
confidence: 53%
“…Blocked neuronal receptors can be recycled from the plasma membrane through endocytosis (Saheki and De Camilli, 2012). Our data indicate that spinosad exposure leads to the removal of Dα6 nAChRs from neuronal membranes (Nguyen et al, 2021) and localization to enlarged lysosomes, resulting in lysosomal expansion ( Figure 2C ) and lysosomal dysfunction.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations